Validation of a Spanish version of the Leicester Cough Questionnaire in non-cystic fibrosis bronchiectasis. (May 2016) - Muñoz, Gerard; Buxó, Maria; de Gracia, Javier; Olveira, Casilda; Martinez-Garcia, Miguel Angel; Giron, Rosa; Polverino, Eva; Alvarez, Antonio; Birring, Surinder S; Vendrell, Montserrat
The Leicester Cough Questionnaire (LCQ) has been validated in non-cystic fibrosis bronchiectasis (NCFBC). The present study aimed to create and validate a Spanish version of the LCQ (LCQ-Sp) in NCFBC. The LCQ-Sp was developed following a standardized protocol. For reliability, we assessed internal consistency and the change in score over a 15-day period in stable state. For responsiveness, we assessed the change in scores between visit 1 and the first exacerbation. For validity, we evaluated convergent validity through correlation with the Saint George's Respiratory Questionnaire (SGRQ) and discriminant validity. Two hundred fifty-nine patients (118 mild bronchiectasis, 90 moderate bronchiectasis and 47 severe bronchiectasis) were included. Internal consistency was high for the total scoring and good for the different domains (Cronbach's α : 0.86–0.91). The test–retest reliability shows an intraclass correlation coefficient of 0.87 for the total score. The mean LCQ-Sp score at visit 1 decreased at the beginning of an exacerbation (15.13 ± 4.06 vs. 12.24 ± 4.64; p < 0.001). The correlation between LCQ-Sp and SGRQ scores was −0.66 ( p < 0.01). The differences in the LCQ-Sp total score between the different groups of severity were significant ( p < 0.001). The LCQ-Sp discriminates disease severity, is responsive to change when faced with exacerbations and is reliable for use in bronchiectasis.